2010
DOI: 10.1007/s12291-010-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Certain Antibiotics Against Filarial Parasite Brugia malayi In Vitro: Possible Role of Oxidative Stress

Abstract: WHO-Tropical Disease Research scheme highlighted the need for development of new anti-filarial drugs. Certain antibiotics have recently been found effective against Wolbachia, co-existing symbiotically with filarial parasites. Inflammatory response entails oxidative mechanism to educe direct anti-microbial effect. In the present study microfilariae were maintained in vitro in medium supplemented with varying concentrations of tetracycline, doxycycline (20-100 lg/ml) or ciprofloxacin (50-250 lg/ml) separately t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Anti-Wolbachia therapy with doxycycline (a semisynthetic derivative of the tetracycline family) has been recommended for the treatment of individuals with lymphatic filariasis and onchocerciasis [8,48,58,84,85,[95][96][97][98][99][100][101][102] (Table 2). It allows the development of filariae in their vector to be blocked, thus arresting the transmission [103,104].…”
Section: Wolbachia As a Filaricidal Targetmentioning
confidence: 99%
“…Anti-Wolbachia therapy with doxycycline (a semisynthetic derivative of the tetracycline family) has been recommended for the treatment of individuals with lymphatic filariasis and onchocerciasis [8,48,58,84,85,[95][96][97][98][99][100][101][102] (Table 2). It allows the development of filariae in their vector to be blocked, thus arresting the transmission [103,104].…”
Section: Wolbachia As a Filaricidal Targetmentioning
confidence: 99%
“…This antibiotic not showed much more activity as other two extracts used. In similar study Ciprofloxacin was shown antifilarial activity against Brugia malayi parasite [23]. Novobiocin antibiotics also found to be active in many experiment against Brugia malayi [24,25].…”
Section: Disscusionmentioning
confidence: 77%
“…Because the Brugia malayi life cycle can be maintained in small mammals, this species is the one used most often for in vitro drug screening studies (132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143). Other filariae used for in vitro drug testing include Brugia pahangi (153), O. volvulus and other Onchocerca species (141,144), L. loa (145), Litomosoides sigmodontis and Acanthocheilonema viteae (filarial nematodes of rodents) (146)(147)(148), and Setaria species (filarial nematodes of sheep, cattle, and other ruminant mammals) (149)(150)(151)(152).…”
Section: Filariaementioning
confidence: 99%
“…For most studies evaluating the effects of potential antifilarial agents, microfilariae are observed on a regular basis for a period of 1 to 7 days, and adult filarial worms are observed for a period of days to weeks (132-136, 138, 140-144, 148, 153). While worms can be identified as simply motile or nonmotile (136,139,140,142,145), in many studies, scoring systems have been applied to characterize the degree of motility observed at different time points (132-135, 138, 143, 144, 148, 151-153).…”
Section: Filariaementioning
confidence: 99%